Magnetic phase diagram and magnetoelastic coupling of NiTiO3 - Dey, Kaustav; Sauerland, Sven; Werner, Johannes; Skourski, Y.; Abdel-Hafiez, M.; Bag, R.; Singh, S.; Klingeler, Rüdiger (Physical review, 2020)
We report high-resolution dilatometry on high-quality single crystals of NiTiO3 grown by means of the optical floating-zone technique. The anisotropic magnetic phase diagram is constructed from thermal expansion and magnetostriction studies up to B=15T and magnetization studies in static (15-T) and pulsed (60-T) magnetic fields. Our data allow us to quantitatively study magnetoelastic coupling and to determine uniaxial pressure dependencies. While the entropy changes are found to be of magnetic nature, Grüneisen analysis implies only one relevant energy scale in the whole low-temperature regime. Thereby, our data suggest that the observed structural changes due to magnetoelastic coupling and previously reported magnetodielectric coupling [L. Balhorn, J. Hazi, M. C. Kemei, and R. Seshadri, Phys. Rev. B 93, 104404 (2016)] are driven by the same magnetic degrees of freedom that lead to long-range magnetic order in NiTiO3.
Im Titel ist die Zahl "3" tiefgestellt
Gesehen am 08.07.2020